Additive manufacturing of alloys with programmable microstructure and properties - Gao, Shubo (2024)
In metallurgy, mechanical deformation is essential to engineer the microstructure of metals and to tailor their mechanical properties. However, this practice is inapplicable to near-net-shape metal parts produced by additive manufacturing (AM), since it would irremediably compromise their carefully designed geometries. In this work, we show how to circumvent this limitation by controlling the dislocation density and thermal stability of a steel alloy produced by laser powder bed fusion (LPBF) technology. We show that by manipulating the alloy's solidification structure, we can 'program' recrystallization upon heat treatment without using mechanical deformation. When employed site-specifically, our strategy enables designing and creating complex microstructure architectures that combine recrystallized and non-recrystallized regions with different microstructural features and properties. We show how this heterogeneity may be conducive to materials with superior performance compared to those with monolithic microstructure. Our work inspires the design of high-performance metal parts with artificially engineered microstructures by AM.